Grain boundary junctions, ridges and facets: their kinetics and effects on grain microstructure evolution. Issue 2 (1st April 2013) - Gottstein, G.; Shvindlerman, L. S.
Abstract : The kinetics of grain boundary triple junctions, grain boundary ridges and grain boundary facets are investigated. A theoretical concept and results of experimental observations and computer simulations of the behavior of these interfacial elements are presented, and their effect on the evolution of grain microstructure in 2D and 3D polycrystals is considered.